Molecular and Morphological Identification of Psychotria sp. Bogor Botanical Gardens Collection - Alifah Nur Anzani; Nia Yuliani; Irfan Martiansyah (Universitas Nusa Bangsa, 2025)
Psychotria is the largest genus in the Rubiaceae family and is considered taxonomically complex due to the limited availability of diagnostic morphological characters. This study aimed to identify a Psychotria sp. spesimen from the Bogor Botanical Gardens using molecular and morphological approaches. The methods included DNA barcoding using the chloroplast rbcL marker, computational analysis with MEGA X, and morphological comparison with Psychotria herbarium spesimens at the Herbarium Bogoriense. BLAST analysis revealed that the Psychotria sp. sample is genetically closely related to P. marginata, P. racemosa, and P. viridis, with each exhibiting 100% identity. Phylogenetic reconstruction placed the spesimen within the same clade as P. marginata, supported by a bootstrap value of 54%. Morphological observations revealed similarities in fruit and flower characteristics with those of P. viridis and P. racemosa.